Soil physical and hydraulic properties in the Donato stream basin, RS, Brazil. Part 1: Spatial variability - Siqueira,Tirzah M. (2019)
ABSTRACT The processes of water flow and water storage in the soil are directly associated with its hydraulic properties, which may vary significantly in space. Therefore, this study aimed to perform a spatial analysis of saturated hydraulic conductivity and the parameters of the soil water retention curve in the Donato basin, located in the municipality of Pejuçara, in the northwest region of the state of Rio Grande do Sul, Brazil, with geographic coordinates between 28º 25’ 34” S and 53º 40’ 30” W, and 28º 24’ 50” S and 53º 41’ 30” W, 590 m of altitude. Undisturbed soil samples (total of 55) were collected from August to November of 2012. The results have demonstrated larger variability for hydraulic conductivity and for the parameter α of the retention curve, and allowed identifying that the high spatial heterogeneity of the studied variables could be associated with factors such as climate, land use and land cover, sampling errors, sampling grid density and also the level of soil compaction.